Optimalisasi dan Implementasi Otonomi Daerah dalam Perspektif Good Governance - Suparman, Odang (AHKAM, 2023)
Based on the 1945 Constitution of the Republic of Indonesia, the government system and state power are administered (meaning that in this case it is held, used and accounted for) by several state institutions, namely the President, the People's Consultative Assembly, the People's Representative Council, the Regional Representatives Council, the Financial Auditor, Supreme Court, and Constitutional Court. The principle used is not the separation of powers like the Trias Politica Theory proposed by Montesquieu, but in practice in Indonesia is the division or separation of powers. For example, the President of the Republic of Indonesia is the head of government and head of state. As head of government, he exercises executive power. In addition, as the head of state, he has the authority to grant clemency, amnesty and abolition in the realm of judicial power.